2023
DOI: 10.1038/s41467-023-40140-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-wave infrared cavity resonances in a single GeSn nanowire

Abstract: Nanowires are promising platforms for realizing ultra-compact light sources for photonic integrated circuits. In contrast to impressive progress on light confinement and stimulated emission in III-V and II-VI semiconductor nanowires, there has been no experimental demonstration showing the potential to achieve strong cavity effects in a bottom-up grown single group-IV nanowire, which is a prerequisite for realizing silicon-compatible infrared nanolasers. Herein, we address this limitation and present an experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…• Stabilizing of the single crystalline diamond lattice by low-dimensional structures (quantum well, quantum wire, quantum dot). Bulk GeSn is only stable up to 1% Sn, but crystalline interfaces stabilize thin epitaxial structures more by up-and down interfaces (wells [35]), all-around interfaces (wires [36]), and island formation (dots).…”
Section: Discussionmentioning
confidence: 99%
“…• Stabilizing of the single crystalline diamond lattice by low-dimensional structures (quantum well, quantum wire, quantum dot). Bulk GeSn is only stable up to 1% Sn, but crystalline interfaces stabilize thin epitaxial structures more by up-and down interfaces (wells [35]), all-around interfaces (wires [36]), and island formation (dots).…”
Section: Discussionmentioning
confidence: 99%
“…Monolithic infrared (IR) solid-state light sources grown on silicon have attracted significant interest owing to their relevance to scalable photonic integrated circuits (PICs) and compatibility with complementary metal-oxide-semiconductor (CMOS) technologies. Among a plethora of applications, this monolithic integration is increasingly crucial to implementing compact and cost-effective IR sensing and imaging technologies. The former requires emitters operating at longer wavelengths in the IR range to overlap with the molecular fingerprint.…”
Section: Introductionmentioning
confidence: 99%
“…21,34,36 These hurdles can be mitigated or eliminated by shrinking the Ge core diameter to enhance the strain relaxation. 37,38 As a matter of fact, modeling studies suggested that a Ge NW with a diameter below 20 nm provides a compliant substrate thereby preventing extended structural defects and Sn segregation, 37,39,40 which can lead to Ge 1−x Sn x shells with better content uniformity while minimizing the compressive strain. 40 Herein, this work puts to test these theoretical predictions and demonstrates the growth of Ge/Ge 1−x Sn x core/shell NWs using a 20 nm Ge core yielding a better control over the Sn content uniformity.…”
mentioning
confidence: 99%
“…Nanowires (NWs) provide, in principle, a promising solution to synthesize Ge 1– x Sn x alloys with higher crystallinity, primarily due to the inherent enhanced strain relaxation along their free sidewall facets. Indeed, the use of Ge NWs as substrates to grow Ge 1– x Sn x has been explored to form heterostructures with limited defects despite the large lattice mismatch. , However, the current studies on Ge/Ge 1– x Sn x core/shell NWs employed a Ge core diameter of 50 nm or larger, systematically resulting in significant compositional fluctuations and defect formation. ,, These hurdles can be mitigated or eliminated by shrinking the Ge core diameter to enhance the strain relaxation. , As a matter of fact, modeling studies suggested that a Ge NW with a diameter below 20 nm provides a compliant substrate thereby preventing extended structural defects and Sn segregation, ,, which can lead to Ge 1– x Sn x shells with better content uniformity while minimizing the compressive strain . Herein, this work puts to test these theoretical predictions and demonstrates the growth of Ge/Ge 1– x Sn x core/shell NWs using a 20 nm Ge core yielding a better control over the Sn content uniformity.…”
mentioning
confidence: 99%